The noise of the miners in Falun 1743 – Court records - Språkbanken Text (University of Gothenburg, 2025)
The Miners’ Uproar in Falun, 1743
For three days in June 1743, Falun was part of what is known as the Dalecarlian Rebellion or the Great
Dalecarlian Dance. The Parliament’s message about conscription had provoked the fury of the common people. All
male inhabitants of Upper Dalarna were called upon via a circular message (budkavle) to "march" to Stockholm to
leave their homes and, if necessary, use force to assert their cause. In Falun, resentment over wages and working
conditions in the mine added fuel to the rebellious atmosphere, growing into rage among some of the miners. The
authorities—mine foremen, clergy, and townspeople—eventually feared for their lives.
Beginning on October 4, 1743, at the urging of the Royal Majesty and Parliament, trials were held against 79
miners and guards.
Where does the dataset come from?
The records are part of the archive series Bergskollegium with reference code SE/RA/420013/02/E II
b/57: Minutes from an extraordinary court session concerning the Dalecarlian commoners’ rebellion, October 4 –
November 12, 1743.
What information is in the dataset?
The transcribed court record consists of over a thousand pages of continuous text, detailing the trial day by
day. It also includes written testimonies, often attached in full. The texts contain information such as the date
of trial, names and titles of defendants, witnesses, and the presiding officials; in some cases, place names and
family relationships are also provided. The data has been transcribed faithfully to the source.

Gruvdrängarnas buller i Falun 1743
Under tre dagar i juni 1743 var Falun en del i det så kallade Dalaupproret eller Stora Daldansen.
Riksdagensbudkavle om soldatutskrivning hade väckt allmogens raseri, och alla invånare i övre Dalarna har genom en
budkavle uppmanats att gå man ur huse för att om nödvändigt med våld hävda sin sak. I Falun spär förtrytelsen över
lönesättning och arbetsförhållanden i gruvan på upprorsstämningen, och växer sig hos somliga gruvdrängar till
raseri. Överheten i form av gruvförmän, prästerskapet och borgarna fruktar till slut för sitt
liv.
Med start den 4 oktober 1743 hölls på Kungl. Maj:t och Riksdagens uppmaning rättegångar mot 79 gruvdrängar och
vaktare.
Var kommer datamängden ifrån?
Protokollen ingår i arkivserien Bergskollegium med referenskod SE/RA/420013/02/E II b/57: Protokoll vid urtima
ting med anledning av dala-allmogens uppror 4 oktober – 12 november 1743.
Vilka uppgifter finns i datamängden?
Den transkriberade domboken består av över tusen skrivsidor med löpande text, som detaljerat refererar
rättegången dag för dag. Där refereras även skriftliga vittnesmål, som ofta är bifogade i sin helhet. I texterna
finns bland annat uppgifter som rättegångsdag, namn och titel på tilltalade, vittnen och presidium; i vissa fall
finns ortnamn och släktskap angivna. Uppgifterna har transkriberats källtroget
Gruvdrängarnas buller i Falun 1743 – Rättegångsprotokoll
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik